2009
DOI: 10.1038/npp.2009.129
|View full text |Cite
|
Sign up to set email alerts
|

The Reward Circuit: Linking Primate Anatomy and Human Imaging

Abstract: Although cells in many brain regions respond to reward, the cortical-basal ganglia circuit is at the heart of the reward system. The key structures in this network are the anterior cingulate cortex, the orbital prefrontal cortex, the ventral striatum, the ventral pallidum, and the midbrain dopamine neurons. In addition, other structures, including the dorsal prefrontal cortex, amygdala, hippocampus, thalamus, and lateral habenular nucleus, and specific brainstem structures such as the pedunculopontine nucleus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

193
2,859
6
23

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,134 publications
(3,145 citation statements)
references
References 283 publications
193
2,859
6
23
Order By: Relevance
“…Dopaminergic neurons in the SN/VTA are associated with expected rewards (D'Ardenne et al, 2008;Schultz et al, 1997) and control of motor responses (e.g., Hikosaka, 1989;Chevalier and Deniau, 1990;Mink, 1996) in decision-making. The thalamus serves as a critical relay structure between cortical and subcortical regions, facilitating information integration among the SN/VTA and striatum as well as prefrontal areas such as the vmPFC and dlPFC (Haber and Knutson, 2009). The vmPFC has been widely implicated in subjective value encoding Kable and Glimcher, 2007;Levy and Glimcher, 2012;Montague and Berns, 2002;Padoa-Schioppa and Assad, 2006;Plassmann et al, 2007) and has been shown to integrate value information during multi-attribute decision-making (Basten et al, 2010;Hare et al, 2011;Kahnt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic neurons in the SN/VTA are associated with expected rewards (D'Ardenne et al, 2008;Schultz et al, 1997) and control of motor responses (e.g., Hikosaka, 1989;Chevalier and Deniau, 1990;Mink, 1996) in decision-making. The thalamus serves as a critical relay structure between cortical and subcortical regions, facilitating information integration among the SN/VTA and striatum as well as prefrontal areas such as the vmPFC and dlPFC (Haber and Knutson, 2009). The vmPFC has been widely implicated in subjective value encoding Kable and Glimcher, 2007;Levy and Glimcher, 2012;Montague and Berns, 2002;Padoa-Schioppa and Assad, 2006;Plassmann et al, 2007) and has been shown to integrate value information during multi-attribute decision-making (Basten et al, 2010;Hare et al, 2011;Kahnt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These regions are highly interconnected with BLA and CMA subregions, forming an amygdalo‐cortico‐striatal circuit dedicated, among other things, to various aspects of reward processing [Haber, 2011; Haber and Knutson, 2010; Naqvi and Bechara, 2009]. Within this circuitry, cortical and striatal regions seem to accommodate reward evaluation (e.g., magnitude, probability, and immediacy) and action planning, while BLA and CMA apparently serve attention modulation and stimulus‐reward learning [Haber, 2011; Haber and Knutson, 2010; Peck and Salzman, 2014]. Reward circuit hyperconnectivity reported here might thus reflect a hyperfunctioning reward system, which in theory could fuel an interpersonal style dominated by rewards and personal gains.…”
Section: Discussionmentioning
confidence: 99%
“…Current conceptions of how reward is processed in the brain propose that a circuit of regions, including the ventral striatum and dopaminergic cells in the ventral tegmental area, is necessary for learning about and using rewards to guide behavior 147 . Several studies have shown that there are age reductions in striatal responses to learned reward 148 , and reward anticipation 149 .…”
Section: Dopaminementioning
confidence: 99%